Lyme periprosthetic joint infection in total knee arthroplasty - Murillo Adrados, MD (Arthroplasty Today, 2018)
Lyme arthritis, caused by the spirochete Borrelia burgdorferi sensu stricto, is a common tick-borne illness in New England and the upper Midwest. Most often, the disease affects the knee and has typically been reported as a cause of native joint infection. There has been only 1 case of Lyme periprosthetic joint infection (associated with a total knee arthroplasty) reported in the literature, and to our knowledge, no other reported cases of Lyme periprosthetic joint infections exist. In this article, we report on 2 patients diagnosed with prosthetic joint infections who were subsequently found to have Lyme prosthetic joint infections, with B burgdorferi as the infectious organism. We discuss the medical and surgical management of these patients.